RISK FACTORS FOR CHRONIC DISEASES IN ELDERLY POPULATIONS - dos Santos da Silva, Miracelia; José Angel, Douglas; Santana da Silva Fontenele, Samara; Renne Silva de Castro, Carlos (Health and Society, 2025)
This study aims to review the literature on risk factors associated with the development of chronic diseases in older populations. The research will address aspects such as lifestyle, socioeconomic conditions, comorbidities, and the influence of preventive interventions. Based on the analysis of recent studies, we hope to identify patterns and correlations that can contribute to improving the health conditions of this population. The relevance of this study lies in the urgent need for public health strategies aimed at the prevention and effective management of chronic diseases in the aging population.